You are on page 1of 2

1. Special Products The following special products come from multiplying out the brackets.

You'll need these often, so it's worth knowing them well. a(x + y) = ax + ay

Answer Example 4: Expand (5a + 2b)2 Answer Example 5: Expand (q 6)2 Answer

(x + y)(x2 xy + y2) = x3 + y3 (Sum of 2 cubes) (x y)(x2 + xy + y2) = x3 y3 (Difference of 2 cubes) These are also worth knowing well enough so you recognize the form, and the differences between each of them. (Why? Because it's easier than multiplying out the brackets and it helps us solve more complex algebra problems later.) Example: Expand (2s+3)3 Answer Exercises Expand:

(x + y)(x y) = x2 y2 (Difference of 2 squares) (x + y)2 = x2 + 2xy + y2 (Square of a sum) (x y)2 = x2 2xy + y2 (Square of a difference) Examples using the special products Example 1: Multiply out 2x(a 3) Answer Example 2: Multiply (7s+2t)(7s2t) Answer Example 3: Multiply (12 + 5ab)(12 5ab) Answer (4) (3p 4q)2 Special Products and Factoring Strategies Review of Three Special Products Recall the three special products: 1. Difference of Squares x2 - y2 = (x - y) (x + y)

Example 6: Expand (8x y)(3x + 4y) Answer Example 7: Expand (x + 2 + 3y)2 Answer Special Products involving Cubes The following products are just the result of multiplying out the brackets. (x + y)3 = x3 + 3x2y + 3xy2 + y3 (Cube of a sum) (x y)3 = x3 3x2y + 3xy2 y3 (Cube of a difference)

(1) (s + 2t)(s 2t) Answer (2) (i1 + 3)2 Answer (3) (3x + 10y)2

2. Square of Sum x2 + 2xy + y2 = (x + y)2 3. Square of Difference x2 - 2xy + y2 = (x - y)


2

Special Products Involving Cubes Just as there is a difference of squares formula, there is also a difference of cubes formula. 4. x3 - y3 = (x - y) (x2 + xy + y2) Proof:

We use the distributive law on the right hand side x (x2 + xy + y2) - y (x + xy + y2)
2

3. x6 - 64 = (x3 - 8) (x3 + 8) = (x - 2) (x2 + 2x + 4) (x + 2) (x2 - 2x + 4)

= x3 + x2y + xy2 x y - xy2 - y3


2

Exercises: Factor the following

5. Now combine like terms to get x3 - y3 Next, we state the sum of cubes formula. 6. x3 + y3 = (x + y)(x2 - xy + y2)

A. 45a3b 20ab3

B. 64x6 - 16x3 + 1

Exercise Prove the sum of cubes equation (Equation 5)

C. x2 + 2xy + y2 81

D. x12 - y12 (Challenge Problem) Using the Special Product Formulas for Factoring

Examples: Factor the following 1. 36x2 - 4y2 = (6x - 2y) (6x + 2y) Notice that there only two terms. Africa, Antarctica, Asia, Australia, Europe, North America, and South America

2. 3x3 - 12x2 + 12x = 3x (x2 - 4x + 4) Remember to pull the GCF out first. = 3x(x -2)2